INOVASI PENGUJIAN KENDARAAN SISTEM DRIVE THRU SEBAGAI UPAYA UNTUK MENGURANGI PRAKTIK PERCALOAN - I Komang Tri Dharma Kesuma (Jurnal Hukum Saraswati (JHS), 2019)
Transportation is very needed today especially in bigcities, this is because transportation plays a very important role in supporting, improving and enhancing economic development both at regional and national levels. Thus motor vehicle testing is one of the public service sectors that plays an important role in supporting the smooth mobility of the community to move in big cities whose purpose is to find out the feasibility of motorized vehicles.However, the existence of brokering practices in every community service provided by the government is sometimes very disturbing, one of the misservice in the motor vehicle testing office. So as to minimize this practice, a new innovation is needed, namely by the issuance of motor vehicle testing innovations with the drive thru system. This research is classified into empirical legal research from descriptive analysis research using primary data and secondary data.